Increasing Customer Loyalty of Islamic Bank Case Study at PT Bank Syariah Indonesia in Semarang - Rodhiati, Annisa Zuhroida; Widowati, Mustika; Windawati, Atif (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
This study aims to investigate the impact of service quality, bank digitalization, and customer relationship management on customer loyalty with customer satisfaction as an intervening. The number of samples was 110 customers of PT Bank Syariah Indonesia in Semarang, who were selected using a purposive sampling technique. The analysis model used in this research is the path analysis model, and the analysis technique uses a simultaneous significance test (F test), partial significance test (t-test), coefficient of determination test (R2), and Sobel test processed with the SPSS 26.00 program. The results show that quality service, bank digitalization, customer relationship management, and customer satisfaction simultaneously significantly affect customer loyalty. Furthermore, service quality, bank digitalization, and customer satisfaction partially have a positive and significant effect on customer loyalty. Meanwhile, customer relationship management partially has a negative and insignificant effect on customer loyalty. Path analysis test results show that customer satisfaction can mediate the influence of service quality on customer loyalty. However, customer satisfaction cannot mediate the influence of bank digitalization and customer relationship management on customer loyalty at PT Bank Syariah Indonesia in Semarang City.